PERAN KUALITAS LAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN MENGGUNAKAN ANALISIS SEM - Stephen Setyadi; Tumpal J.R. Sitinjak (Jurnal Cakrawala Ilmiah, 2026)
The purpose of this study was to determine the effect of service quality through customer satisfaction. The data used in this study were primary data. Primary data were collected through questionnaires distributed to 75 respondents who had been a member Best Fitness Lotte Mart more than one month. The sampling technique using non-probability sampling using judgment sampling method. The analytical method used was descriptive analysis and Structural Equation Modeling (SEM) based variants using Partial Least Square (PLS). From the existing analysis, can be found that service quality proven influence on customer satisfaction.